2004
DOI: 10.1111/j.1541-4337.2004.tb00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Microorganisms to Cold Temperatures, Weak Acid Preservatives, Low pH, and Osmotic Stress: A Review

Abstract: The application of physical stress to microorganisms is the most widely used method to induce cell inactivation and promote food stability. To survive, microorganisms have evolved both physiological and genetic mechanisms to tolerate some extreme physical conditions. This is clearly of significance to the food industry in relation to survival of pathogens or spoilage organisms in food. In some microorganisms, the "cold shock response" has been observed in response to abrupt changes to lower temperatures. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
376
0
26

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(416 citation statements)
references
References 251 publications
(211 reference statements)
14
376
0
26
Order By: Relevance
“…Sorbic acid (trans-trans-2,4-hexadienoic acid) is a six-carbon unsaturated fatty acid with a pK a of 4.76 and was first isolated from unripe berries of Rowan (Sorbus aucuparia). The acid, or its anionic salt, is used in a variety of food products and has a broad range of antimicrobial activities against spoilage bacteria, yeasts, and molds (5,17,57). However, the exact mechanism by which sorbate inhibits microbial growth is not entirely understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sorbic acid (trans-trans-2,4-hexadienoic acid) is a six-carbon unsaturated fatty acid with a pK a of 4.76 and was first isolated from unripe berries of Rowan (Sorbus aucuparia). The acid, or its anionic salt, is used in a variety of food products and has a broad range of antimicrobial activities against spoilage bacteria, yeasts, and molds (5,17,57). However, the exact mechanism by which sorbate inhibits microbial growth is not entirely understood.…”
mentioning
confidence: 99%
“…Depending on the species, bacteria can induce several systems to counteract a drop in the internal pH when encountering low pH stress. Among others, these include proton pumps, several decarboxylases (lysine, glutamate, and arginine), the production of urease, arginine deiminase, chaperones (e.g., DnaK and GroELS), and sigma factor (SigB, SigM, and RpoS)-mediated responses (5,6,14,31,67). However, the importance of low-pH stress response systems in weak-acid resistance development remains unclear.…”
mentioning
confidence: 99%
“…As referred by Gabriel (2013) aside from some protection conferred by solutes against heat injury, the decrease in a w also brings forth physical damage to cellular membranes and provides reduction of intracellular moisture which can negatively affect the function of cellular enzymes. Exposures to IJFS October 2017 Volume 6 pages 139-151 acidic environments are also known to induce disruption of biochemical processes within the cells such as enzymes functions and nutrient transport (Beales, 2004). At higher temperatures, the study of Aljarallah and Adams (2007) showed that ribosomal inactivation was a primary target of cell damage.…”
Section: Effect Of Plating Mediamentioning
confidence: 99%
“…An additional 19 promoters with changes in their -35 and -10 regions have been part of the Registry of Standard Biological Parts since 2004(MIT Working Group, 2005. The sequence of each mutant promoter is presented along with relative strengths determined by RFP expression data (http://parts.igem.org/Part:BBa_J23100).…”
Section: Applications Using Promoters With Varying Strengthsmentioning
confidence: 99%
“…For example, human brain cells need to express certain genes that are not needed in muscle cells, and vice versa (Gurdon & Melton, 2008). In a similar sense, bacteria must express different genes depending on temperature, pH, osmotic pressure, or the availability of food (Beales, 2004). Knowledge of gene regulation is important for understanding the differentiation and function of eukaryotic cells, the development of tissues in multicellular organisms, and the relationships of bacteria to their environments throughout the biosphere.…”
Section: Introductionmentioning
confidence: 99%